Tekanan Optimalisasi Laba terhadap Reaksi Pasar dengan Tax Avoidance sebagai Variabel Mediasi: (Studi Kasus: Perusahaan Sub Sektor Asuransi yang terdaftar di Bursa Efek Indonesia Tahun 2020 – 2023) - Frana, Frana; Kusuma, Marhaendra; Athori, Agus (Akuntansi Pajak dan Kebijakan Ekonomi Digital, 2025)
This research aims to examine the effect of profit optimization on market reaction and the mediating role of tax avoidance in this relationship among insurance sub-sector companies listed on the Indonesia Stock Exchange during the 2020–2023 period. Profit optimization is proxied by Return on Assets, market reaction by stock returns, and tax avoidance by the Effective Tax Rate. This research employs a quantitative approach using secondary data obtained from the financial statements of 17 insurance sub-sector companies, with a final sample of 10 companies selected through purposive sampling. Data analysis was conducted using classical assumption tests, multiple linear regression, and path analysis. The results indicate that profit optimization has a positive and significant effect on tax avoidance. However, tax avoidance does not influence market reaction, and profit optimization also does not have a direct effect on market reaction. Furthermore, tax avoidance is able to mediate the effect of profit optimization on market reaction. This study contributes to a deeper understanding of how earnings information quality, taxation strategies, and investor responses interact in shaping capital market dynamics within the insurance industry. The findings also provide a foundation for future research to explore external factors that may influence these relationships, offering additional academic value for strengthening subsequent studies.